SERVICE QUALITY AND CONSUMER PATRONAGE IN ROBAN STORES, AWKA ANAMBRA STATE-NIGERIA: CONTENT ANALYSIS - Ndidiamaka, Okoye Joy; Nwokike, Chidi E. (Indonesian Marketing Journal, 2023)
This study explores the relationship between service quality and consumer patronage at Roban Stores, Awka, Anambra State, Nigeria, employing a qualitative research approach through content analysis. Service quality is conceptualized as the provider's ability to meet customer expectations and enhance business performance through dimensions such as reliability, responsiveness, assurance, empathy, and tangibles. Consumer patronage is defined as the consistent preference of consumers to repeatedly choose a particular firm's products or services over competitors', influenced by factors including product quality, price competitiveness, customer service, and overall satisfaction. The study investigates these dynamics at Roban Stores, high lighting factors such as quality products, competitive pricing, excellent customer service, strategic location, diverse product offerings, promotional activities, store ambiance, word-of-mouth, loyalty programs, and social media presence as crucial in shaping consumer perceptions and fostering patronage. Findings underscore the significance of managing service quality to enhance customer satisfaction and loyalty, recommending strategies for continuous improvement to sustain competitive advantage in the retail market.